Respon Pupuk Organik Cair Urin Kelinci Terhadap Pertumbuhan dan Hasil Tanaman Buncis (Phaseolus vulgaris): Response of Liquid Organic Fertilizer from Rabbit Urine on The Growth and Yield of Green Beans Plants (Phaseolus vulgaris) - Krisnarini; Vera Prawestiana; Miandri Sabri Pratama (Planta Simbiosa, 2023)
This research aims to determine the effect of liquid organic fertilizer (POC) concentration in rabbit urine on the growth and yield of green beans plants. The research used a simple randomized block design consisting of five treatments and repeated five times. Treatment consists of: A (dose 5 ml/liter), B (dose 15 ml/liter), C (dose 25 ml/liter), D (dose 35 ml/liter), E (dose 45 ml/liter); and plant response variables consist of: plant height, plant dry weight, number of pods per plant, pod weight per plant, pod length per plant. The research results showed that the application of different concentrations of rabbit urine liquid organic fertilizer had the same effect on plant height and plant length per plant but had a different effect on plant dry weight, number of pods per plant, and pod weight per green beans plant.